Evaluasi sistem drainase menggunakan pemodelan HEC-RAS: Studi kasus Jalan Puloampel Bojonegara KM 17-18 Kabupaten Serang, Banten - Aldi; M. Oka Mahendra (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Drainage problems along the Puloampel–Bojonegara Road in Serang Regency, Banten, have become a concern due to frequent waterlogging during the rainy season, where the dimensions or size of the drainage channels cannot accommodate the existing flow rate of 3,01 m³/sec, which causes water to overflow. In addition to impairing road user comfort, this flooding damages road infrastructure, raises the possibility of traffic accidents, and interferes with logistics distribution in the nearby industrial regions. This study aims to evaluate the performance of the existing drainage system and provide technical recommendations using HEC-RAS-based numerical modeling. The data used includes primary data from field surveys in the form of existing channel condition data, channel geometry data in the form of channel width and depth, channel slope, channel cross-sectional shape and secondary data such as rainfall data and land use data. Hydrological analysis was carried out using the Log Pearson Type III distribution to determine the design rainfall, while the discharge was calculated using the Manning equation. The results of the HEC-RAS simulation show that the existing channels have varying dimensions, where the width of the channel is 50 cm – 60 cm, and the height of the channel is 50 cm – 70 cm, which causes the drainage channel to be unable to accommodate flood discharge or flow discharge, with an average overflow height of 30 cm and a maximum of 61 cm. After geometric improvements were made to the channel by widening the channel to 100 cm and deepening the channel to 100 cm, re-simulation showed that all cross-sections were able to accommodate the flow, with an average water level of 35 cm below the edge of the channel. This study offers insightful technical information about the value of regular maintenance and the efficacy of drainage upgrades .